2004
DOI: 10.1602/neurorx.1.4.472
|View full text |Cite
|
Sign up to set email alerts
|

Immune problems in central nervous system cell therapy

Abstract: Summary:Transplantation of cells and tissues to the mammalian brain and CNS has revived the interest in the immunological status of brain and its response to grafted tissue. The previously held view that the brain was an absolute "immunologically privileged site" allowing indefinite survival without rejection of grafts of cells has proven to be wrong. Thus, the brain should be regarded as a site where immune responses can occur, albeit in a modified form, and under certain circumstances these are as vigorous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
90
2
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(98 citation statements)
references
References 94 publications
0
90
2
4
Order By: Relevance
“…Of course, immune rejection and the broader context of inflammation also enter into this equation, given the common desire to utilize transplants in the context of deteriorative diseases or trauma-related damage. While it is arguable that convincing the immune system not to overreact has been extensively studied as a factor in this context (e.g., [64]), the inflammatory response certainly has the capacity to tailor the very adaptation mechanisms we will discuss (e.g., [65]). For extensive reviews of the reciprocal interactions between neural systems and inflammatory systems relevant to plasticity see Di Filipo and colleagues [66], or Xanthos and Sandkuhler [67].…”
Section: Achievements Of "Successful" Transplantationsmentioning
confidence: 99%
“…Of course, immune rejection and the broader context of inflammation also enter into this equation, given the common desire to utilize transplants in the context of deteriorative diseases or trauma-related damage. While it is arguable that convincing the immune system not to overreact has been extensively studied as a factor in this context (e.g., [64]), the inflammatory response certainly has the capacity to tailor the very adaptation mechanisms we will discuss (e.g., [65]). For extensive reviews of the reciprocal interactions between neural systems and inflammatory systems relevant to plasticity see Di Filipo and colleagues [66], or Xanthos and Sandkuhler [67].…”
Section: Achievements Of "Successful" Transplantationsmentioning
confidence: 99%
“…The CNS was thought to exhibit this privilege because blood-brain barrier protection, antigen-presenting cell paucity and limited lymphatic drainage prevented efficient adaptive immune response activation. Because cellular grafts survive long term in the human CNS without immunosuppressant therapy (Freed et al 2001), few transplant studies have fully assessed the role of inflammation in graft survival or long-term function (for excellent reviews on mechanisms governing graft rejection see Barker & Widner (2004) and Bradley et al (2002)). However, post-mortem examinations of foetal mesencephalon-derived graft recipients (independent of the post-transplant immunosuppressant regime) reveal activated microglia and host immune cell infiltration at the host-graft interface and throughout the graft (Freed et al 2001;Olanow et al 2003), strongly suggesting that inflammation compromised graft survival and functional outcome.…”
Section: Missing Links and Next Steps (A) Cell Programming Strategiesmentioning
confidence: 99%
“…Cells transplanted into parenchyma survive better than those transplanted periventricularly (Barker & Widner 2004), potentially owing to proximity to infiltrating antigen-presenting cells near periventricular zones. The probability of immune system-mediated graft rejection also increases with the degree of trauma produced by the transplant procedure.…”
Section: Missing Links and Next Steps (A) Cell Programming Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…By expansion in an in vitro system, adult stem cells can provide enough seed cells for cell transplantation [13,14]. Furthermore, adult stem cells are attractive candidates for cellular therapies, due to the distinct advantages of autologous availability and any ethical concerns associated with other stem cells [15]. Recently, it was shown that adipose tissue-derived mesenchymal stromal cells have the differentiation potential to become RPE-like cells [16,17].…”
Section: Introductionmentioning
confidence: 99%